Traditions of the Russian Popular Science Journalism in the Socio-Cultural Context - Balashova, Yuliya B. (European Scientific Journal, ESJ, 2019)
The article is devoted to the historically established dominants of the science mediatization in Russia. As the main channel of the popular knowledge, the popular science press was segregated. The historical experience of the popular science journalism development shows it’s steadily focused on the commonwealth of the sciences, and audience worldview formation. From the modern terminology point of view, the very model of the Russian popular science press should be determined as a trans-media, or hybrid media, with an organic combination of the educational, enlightenment and entertainment functions.